PENDEKATAN KOMUNIKASI ANTARBUDAYA DALAM INTERAKSI DAN HARMONI ANTARAGAMA - Thadi, Robeet (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
Interfaith communication in a pluralist society can be avoided, in interaction with people of different religions instead of culture, an awareness of differences is needed. This study aims to explain what approaches and barriers to intercultural communication are in fostering interfaith harmony attitudes. This research is a qualitative study, using library research methods or literature review, data is taken from books, magazines, documents and journals both national and international, especially those related to and the object under study. In the context of intercultural communication, there are two approaches that can be used as a combination to study interfaith communication, namely the social psychology approach and the symbolic interactionism approach.